Integrating academic service learning into higher education business curriculum - Moran, Wilfredo (Journal of Management and Business Education, 2024)
This paper discusses an Academic Service Learning (ASL) approach as a teaching method to combine meaningful service to the community and core academic requirements for learning accounting. The Academic Service-Learning approach offers an opportunity for the students to enhance what they are learning in the classroom and combine it with the benefit of providing a service to the community. This study shows how service learning offers a unique opportunity to bridge the gap between academic accounting core curriculum requirements and the need of society to have individuals willing to give their time and effort to benefit others in need. This article aims to understand the benefits of High-Impact practices (HIPs) for students in the classroom, particularly, using Academic Service-Learning as a pedagogical tool. The goal is to understand the benefits of using a Service-Learning approach to teach accounting. As part of the course learning requirement, students engaged in a project whereby a not-for-profit organization's income statement was forecasted and evaluated using a vertical analysis. A post-survey was administered, which focused on how the Service-Learning project helped the students connect what they were learning in class with the actual accounting practice meaningfully.